Livestock services delivery during COVID-19 lockdown: An appraisal of accessibility and constraints - SINGH, BRAJ PAL; CHANDER, MAHESH; PATHADE, SANTOSH S.; PORDHIYA, KISHORE (The Indian Journal of Animal Sciences, 2021)
COVID-19 has devasted many sectors of Indian economy including livestock sector which got more turmoil during the lockdown period. With an intuition to find out the appraisal of livestock management and health services accessed by the farmers and delivered by the private veterinary practitioners, the present study was conducted in Uttar Pradesh. The production parameters, viz. milk production, sell, consumption and utility pattern of milk similarly the pattern of milk supply chain was studied and compared before and during lockdown period. The results revealed that except milk consumption remaining parameters showed negative trend as compared to before lockdown, and dairy co-operative has played a major role in maintaining the milk supply chain during lockdown. The major constraints perceived by the farmers during lockdown were accessed and it was observed that increase in price of feed and fodder followed by fear of corona were major problems. The delivery of livestock services viz. AI, treatment, livestock extension and vaccination by the private veterinary practitioners was accessed and compared before lockdown and during lockdown period. The results revealed that less number of cases attended during lockdown due to low response from farmers for availing the service from them, and fear of corona virus.